Roles of hepatic stellate cells in NAFLD: From the perspective of inflammation and fibrosis - Man Wang; Lei Li; Yannan Xu; Juan Du; Changquan Ling (Frontiers Media S.A., 2022)
Non-alcoholic fatty liver disease (NAFLD) has become one of the most common diseases and severe problems worldwide because of the global increase in obesity, dyslipidemia, hypertension, and type 2 diabetes mellitus. NAFLD includes a wide spectrum of liver diseases, the histological forms of which range from non-alcoholic fatty liver (NAFL), which is generally nonprogressive, to non-alcoholic steatohepatitis (NASH), which can progress to chronic hepatitis, liver cirrhosis (LC), and sometimes hepatocellular carcinoma (HCC). Unlike NAFL, as the progressive form of NAFLD, NASH is characterized by the presence of inflammation with or without fibrosis in addition to hepatic steatosis. Although it is widely known and proved that persistent hepatic injury and chronic inflammation in the liver activate quiescent hepatic stellate cells (HSCs) and lead to hepatic fibrosis, the three-step process of "inflammation-fibrosis-carcinoma" in NAFLD has not been investigated and clarified clearly. In this process, the initiation of inflammation in the liver and the function of various liver inflammatory cells have been discussed regularly, while the activated HSCs, which constitute the principal cells responsible for fibrosis and their cross-talk with inflammation, seem not to be investigated specifically and frequently. Also, accumulated evidence suggests that HSCs can not only be activated by inflammation but also participate in the regulation of liver inflammation. Therefore, it is necessary to investigate the unique roles of HSCs in NAFLD from the perspective of inflammation and fibrosis. Here, we review the pivotal effects and mechanisms of HSCs and highlight the potential value of HSC-targeted treatment methods in NAFLD.